Behavioral Responses to Familiar Versus Unfamiliar Older People as a Source of Disgust. (January 2022) - Cao, Quan; Sun, Jian; Peng, Ming; Chen, Bin-Bin
Disgust, as a part of the behavioral immune system, leads people to avoid behaviors of pathogens so as to reduce the probability of infection. Disgust also shows the source effects based on familiarity. However, these source effects have not been tested on the older population. Thus, we tested the source effects of emotional and behavioral reactions from the disgust toward older adults and the possible moderating effects of filial piety on disgust. In the first study, we employed the self-report method to test the source effects of emotional feelings of disgust amongst undergraduates. In the second study, we measured whether filial piety among community adults produced moderating effects of the disgust toward older adults. In the third study, we employed the shape discrimination task to test the source effects of behavioral avoidance to older adults among undergraduates. The first and third studies show stronger negative emotional/avoidance reactions towards unfamiliar older adults than familiar older adults, affirming the source effects of disgust towards older adults that we expected. However, we did not find moderating effects of filial piety associated with disgust. These findings can help us understand the evolutionary origin of disgust toward older adults, which is likely activated more intensely and quickly in response to unfamiliar individuals as compared with familiar individuals.